The Dual Nature of Devotion: Bestowing Significance Upon One's Existence, or Squandering One's Life - Demir, Songul (ANADOLU ILAHIYAT AKADEMISI, 2026)
Purpose: Devotion is often understood as an excessive and potentially destructive form of commitment associated with self-neglect, impaired judgment, and ethical transgression. However, such a one-sided interpretation obscures its productive and meaning-generating dimensions. The aim of this study is to examine devotion as a complex phenomenon that can be both life-enhancing and life-distorting and to clarify the conditions under which devotion contributes to or undermines human flourishing. Method: The study adopts a qualitative approach grounded in philosophical psychology and employs phenomenological description as its primary analytical method. Conceptual analysis is used to examine the structure of devotion through illustrative cases drawn from philosophy, science, and everyday life. Findings: The analysis reveals that devotion has a dual structure that cannot be adequately evaluated as either inherently pathological or inherently virtuous. Its significance depends on two central criteria: the rationality of the pursued path and the extent to which ethical principles are preserved. When these criteria are met, devotion functions as a source of meaning, perseverance, and creative productivity; when they are violated, devotion may distort the subject's relation to reality and negate the self. Conclusion: By articulating a balanced conceptual framework, this study contributes to contemporary debates on devotion by accounting for both its constructive and destructive potentials. It offers a theoretically grounded perspective that challenges reductionist interpretations and highlights devotion's role in meaning-making practices. The findings also provide conceptual guidance for future philosophical and psychological research on commitment, meaning, and ethical agency.
Keywords: Psychology; Philosophy of Psychology; Devodition; Commitment; Phenomenological Analysis; Meaning; Religion